Optimalisasi Pertumbuhan Bakteri Propionibacterium Acnes pada Media Nutrien Agar - Nadia Budi Agustina; Nadya Bening Putri Febriyani; Piana Astuti; Tessalonika Ersaputri; Liss Dyah Dewi Arini (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Propionibacterium acnes is an anaerobic bacteria that plays an important role in dermatological research, especially in the context of skin diseases such as acne vulgaris. This study aims to optimize the growth conditions of Propionibacterium acnes in sodium media in order to increase the effectiveness of bacterial culture on a laboratory scale. The parameters tested include media pH, sodium concentration, incubation temperature, and incubation time. The research method was carried out systematically and controlled with a completely randomized design using several environmental condition treatments. The results showed that optimal growth of Propionibacterium acnes was achieved in media with a pH of 6.5–7.0, a sodium concentration of 1.5%, an incubation temperature of 37°C, and an incubation time of 72 hours in conditions without oxygen (anaerobic). By knowing the right conditions, Propionibacterium acnes bacteria can grow faster and optimally, so that it can help in dermatological research or product development related to skin health.